The basis for judges' considerations in imposing criminal punishment that are relatively light for convicts in cases of valuable goods proceeding - Dimas Arif Tri Kurniawan; Muhammad Iqbal; Anhar Nasution; Jummaidi Saputra; Wiradmadinata Wiradmadinata (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
Article 480 point 1 of the Criminal Code states that committing certain acts, which include selling and buying, of goods that are known or reasonably suspected to have originated from a crime, are categorized as a crime of collection. The purpose of this research is to explain the causes of the criminal act of collecting valuables. the factors considered by the judge in imposing a relatively light sentence on the perpetrator of the crime of collecting valuables. and countermeasures carried out against the criminal act of collecting valuables. This research uses normative method. The data in writing this thesis were obtained through library research and field research. library research to obtain secondary data by studying legislation, books, and opinions of legal experts relating to the issues discussed, while field research is intended to obtain primary data by interviewing respondents and informants. The results showed that the crime of collecting valuables was to seek profit, then followed by economic and environmental factors. Thus, internal factors or perpetrators are more dominant as a driving factor for the crime of collecting valuables in the jurisdiction of Banda Aceh City. The factors considered by the judge in imposing a relatively light sentence were that the defendant had never been prosecuted, the motive factor and background for committing the crime and the age factor. There are two ways to deal with the crime of collecting valuables, namely preventive efforts and repressive efforts. It is suggested that the sentence handed down must be maximally in accordance with the prosecutor's demands. Vigilance and suspicion must always be exercised and it is hoped that all law enforcement officials will continue to pay attention to the public interest and the rights of a defendant guaranteed by law.